Website Design for Frozen Foods Sales: Perancangan Website Untuk Penjualan Frozen Food - Kusuma, Melvin Aryadika; Gusti, Alexander Kenzy Pinaring; Budiman, Arief (Universitas Muhammadiyah Sidoarjo, 2023)
The study investigates the impact of website utilization in advertising and information distribution, focusing on the case of Frodz—a company utilizing its website as a marketing vehicle and information medium. Employing the Waterfall model, a widely used sequential linear approach in system analysis, the website's development process was analyzed. The goal was to explore how the website effectively and efficiently serves as a promotional and informational platform for Frodz. Results indicate that the website successfully facilitates marketing and publicizing information, products, and promotions, thus enhancing Frodz's outreach and communication with the target audience. Highlights: The utilization of the website as a marketing tool and information medium positively impacted Frodz's promotional efforts, resulting in enhanced reach and effectiveness. Through the Waterfall model approach, the website's development process was systematically analyzed, ensuring a well-structured and efficient platform for advertising and information dissemination. The website played a crucial role in showcasing Frodz's product quality, utilizing promotions and advertisements to engage the public effectively.